VPH-1 Turning Research into Results: Characterizing the Dog Meat Trade in Bali to Help End the Trade - Maria Maliga Vernandes Sasadara; Ni Putu VT Timur; I Ketut Puja; Nyoman S Dharmawan; Jennifer Hood (Hemera Zoa, 2018)
The dog meat trade (DMT) in Bali is a black-market trade that threatens international tourism on both animal welfare and human health grounds. Outlets selling dog meat often advertise this by displaying ‘RW’ signs as this abbreviation stands for ‘rintek wuuk’ (soft fur) in Manadonese. The DMT is notoriously cruel and uses inhumane methods to catch, transport, and slaughter dogs, many of which are believed to be stolen.Dog meat is not a food under Indonesian law and as such is not subject to food safety or zoonotic disease regulation. In particular, the DMT is believed to contribute to the transmission of rabies, which is endemic in Bali.Despite this, there was little factual information about the DMT in Bali, and this was hindering Government efforts to close the trade. We believe our study is the first to characterize the DMT in Bali and provides insights as to how and why the trade exists, and what actions are needed to end it.